Using Relational Dialectic Theory in the tradition of gift-giving in the Indonesian Education environment - Arsyah Putra , Rizky Ramadhani; Utari, Prahastiwi; Sudarmo, Sudarmo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Education, which is one of the